Time is money: o efeito temporal das estratégias políticas corporativas - Lana, Jeferson (2017)
In this thesis, I propose that time can be understood as a performance variable of corporate political strategies - CPS. The rationale behind this proposition is that, by engaging with the political are through campaign donations as a form of political connection, firms obtain, among other effects, greater speed in the responses of processes involving governmental decisions. Speed is seen as a consequence of political alignment between business and government. Based on a database that includes all the decisions of antidumping measures requested by the Brazilian companies between 2001 and 2017, two hypotheses tested the effects of the CPS in the time of decision of such measures. For the tests, multivariate linear regression with robust coefficients and treatment of the variables were used from the concepts of the regression discontinuity design. The results show that political connections increase the speed of decisions on antidumping measures. The results also suggest that the greater the political capacities of the firms, measured by the constancy of the political involvement, the shorter the waiting time for the final decision of the mentioned measures. Thus, this thesis contributes to the evolution of the CPS area by bringing a new relevant face to the debate on the effects of political connections: time. If time is money, the speed of government decisions may be the new golden pot of our time.